Formation of eutectic carbides in Fe–Cr–Mo–C alloy during non-equilibrium crystallization. (15th March 2016) - Wieczerzak, K.; Bala, P.; Stepien, M.; Cios, G.; Koziel, T.
Abstract: The aim of this study was to characterize the eutectic carbides formed in an as-cast hypoeutectic Fe–25Cr–5Mo–0.82C alloy and also to determine their formation sequence during non-equilibrium crystallization. The alloy was synthesized in an arc furnace filled with high purity argon atmosphere and re-cast in a water-cooled copper mould. Optical emission spectrometry, scanning electron microscopy (SEM) energy dispersive spectroscopy (EDS), electron back-scattered diffraction (EBSD) and X-ray diffraction (XRD) analysis were used in the characterization process. The experimental results were compared with the Thermo-Calc based thermodynamic calculations. The alloy consists of ferrite (Fe–Cr–Mo solid solution) and complex eutectic carbides with varying molybdenum and chromium contents. The eutectic M7 C3 and M23 C6 carbides formed in the interdendritic zones exhibit continuous and complex shapes. It was found that non-equilibrium crystallization promotes precipitation of carbides with greater carbon content such as M7 C3 and M23 C6 instead of M6 C. Graphical abstract: Highlights: The hypoeutectic Fe–25Cr–5Mo–0.82C was synthesized in an arc furnace in high purity argon atmosphere and crystallized on a water-cooled copper mould Influence of non-equilibrium crystallization to phase composition was studied Experimental results were compared with thermodynamic analysis of the system Non-equilibrium crystallization promotes precipitation of carbides with greater carbon content such as M7 C3 and M23 C6 instead of M6 C